Persuasion and biasness in interviews on Muammar Gaddafi: an interpersonal analysis / Huzaifah A. Hamid - Huzaifah, A. Hamid (2014)
The current study seeks to investigate the meanings embedded in the media, specifically the biases and persuasion strategies used by interactants in media interviews. It applies Halliday’s theory of Systemic Functional Linguistic (Halliday, 1978; 1994, Thompson, 2004, Martin, Mathhiessen & Painter, 1997, Droga & Humphrey, 2002, Martin & White, 2005) in analyzing the use of Mood, Modality, and Affect made by the interactants in television interviews. The study aims to explore the interpersonal meanings expressed by the interviewers and interviewees through the selection of Mood, Modality, and Affect, and how the foregrounding or absence of such interpersonal meanings are related to the conviction and biases carried in media interviews. Data were collected from two transcripts of television interviews on the death of the Libyan leader, Muammar Gaddafi. Previous studies show incomprehensive findings whereby the analyses were carried out on one interactant, either the interviewer or interviewee instead of both. They also failed to analyse all of the three elements crucial in expressing interpersonal meanings, namely the Mood, Modality and Affect. The present study however analyzes both interactants’ use of language and includes all of the three elements mentioned above. The findings show that the posing of questions in the form of WHinterrogatives is more dominant in matters regarding the death of Gaddafi, emphasizing the interviewers’ use of Mood choices that is driven by the desire to put less pressure on the interviewees. On the other hand, in discussing other matters; the use of yes/no interrogatives is more dominant, proving that the interviewers are willing to put higher pressure on the interviewees in minor issues. For the use of Modality, the inclusion of Metaphors of Modality and the emission of Modality sources were found to be more dominant in the second transcript, suggesting that those interactants are more extremes in expressing their personal thoughts. This can be associated with the mediocre position they hold in society, thus allowing them to have more freedom in expressing their thoughts. The use of Modality by the interviewee in the first transcript is more limited, due to the higher social position he carries as the President of the United States. The interviewers from both transcripts tend to attribute emotions to other people, through the use of negative and positive Affect, subsequently camouflaging their own personal feelings by highlighting the appraised instead of the appraiser. The insights gained from this study may contribute to an understanding of the interpersonal meanings expressed in the media by detecting the persuasion and biases embedded in them. Consequently, people may be able to make their own decision without being manipulated by the media.